QUANTITATIVE DETERMINATION OF VITAMINS A, B1, B2 AND B6 IN PALMYRA FRUITS MARKETED IN GOMBE METROPOLIS - Danbature, W. L.; Fai, F. Y.; Khadijat, M. M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
The study was carried out to determine the amount of vitamin A (retinol), B1 (thiamine), B2 (riboflavin) and B6 (pyridoxine) in Palmyra fruit. The fruits were purchased from Gombe market. One (1) g in 100ml of each of the fruit extract was freshly prepared and used for the analysis. UV/Visible spectrophotometer (model 5400/5405) was used to quantify these vitamins. The results obtained for vitamins A, B1, B2 and B6 were 8.89±0.03 μg/100g, 0.0 mg/100g, 0.03±0.006 mg/100g and 3.50±0.20 mg/100g at λmax 335,747,445 and 465nm respectively. It could be concluded that the consumption of palmyra fruits should be encouraged as it is rich in vitamins.